MAKING YOUR OWN PHOTOMICROGRAPHY LIGHT - Babulski D. (My University, 2002)
Focuses on the importance of light sources in the discipline of mineral micromounting. Sufficiency of a typical high-intensity incandescent table lamp; Factors influencing the production of true color images; Use of a filtered fiber-optic light source to solve illumination problem.
Keywords: LIGHT SOURCES